Development of automotive industry in developing countries during the last two decades - Saraei, Mehrdad (My University, 2020)
In recent century, globalization has appeared as one of the fundamental and powerful drivers forming the world economies. The automobile industry is one of the key industries which determines the economic power of different countries. During the last two decades the Global Value Chains (GVCs) in automotive industry have faced with considerable transformations. The economic crisis 2008-2009 has shifted the automotive industry to developing countries and increased the significance of some large growing economies such as China and India. This master thesis was conducted in order to investigate the circumstances of automotive industry from the past to present especially during the last two decades. The literature review highlights the globalization and its substantial effects to the car industry in developing countries. Literature review has proven that the Foreign Direct Investment (FDI) plays a significant role in the development of the automotive industry in developing countries. Also, the literature review highlights the significance of developing countries in mitigation of greenhouse emissions by presentation of electric vehicles (EVs) to their people and creation of consumption patterns for this production. To answer the research question author used secondary data from different secondary data re-sources. These data analysis helped the author to determine the trend of automobile industry development in developing countries. Results from this study showed the positive effects of globalization to the automotive industry in developing countries. The transformation of global value chains and globalization resulted in considerable development to the automotive industry in developing countries.
Keywords: Electric vehicles, Foreign Direct Investment, Global Value Chains